Resilience and Human History Multidisciplinary Approaches and Challenges for a Sustainable Future - Nara, Yumiko; Inamura, Tetsuya; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2020)
This unique book provides a platform for resilience research, combining knowledge from various domains, such as genetics, primatology, archeology, geography, physical anthropology, cultural anthropology, medicine, ecology, psychology, risk management and systems science, in order to examine specific concepts. The term "resilience" was originally used in psychology, but in current-day usage, it mainly refers to the "ability to recover from disaster"; however, the concept of resilience is still ambiguous. This book challenges readers to reconsider the concept of resilience comprehensively from diverse perspectives and to re-conceptualize it as an important framework applicable in various research fields. The book explores resilience by expanding the time and space scales to the maximum. On the time axis, it traces back to our human ancestors (and even to anthropoid apes) and follows the evolution of humans, the origin of agriculture, the rise and fall of ancient civilizations, and the present day. On the space axis, it discusses levels ranging from genetic; bacterial flora; individual, indigenous communities; and modern societies; to the global level. As such it expands the base for considering the problems facing modern society and selecting a future direction. In the long history of evolution, we Homo sapiens have faced, and overcome, various kinds of risks. By acquiring resilience, we have surpassed other animals and become apparent rulers of the earth; but, at the same time, we are also facing more serious risks than ever before. This book provides insights into addressing the challenges of a sustainable future.
Chapter 1. Resilient Features which Humans Inherited from Common Ancestors with Great Apes and Strengthened -- Chapter 2. Using Genetics to Understanding the Evolution of Human Resilience -- Chapter 3.Individual Differences in Psychological Resilience -- Chapter 4. Human Evolution and the Implication of Resilience for the Future -- Chapter 5. Pastoral Nomadization in the Neolithic Near East: Review from the Viewpoint of Social Resilience -- Chapter 6. Infectious Diseases: Conquest or Co-existence? -- Chapter 7. Resilience in the Andes: Ancient Civilization and Indigenous Society -- Chapter 8. Resilience amongst Nomads and Urban Residents in Mongolia$1 (Bs Transition to a Market Economy -- Chapter 9. Dynamic Resilience of Ayta community: Creative Rehabilitation after Mt. Pinatubo Eruption 1991 -- Chapter 10. Resilience of Life (Livelihood) and Natural Disasters -- Chapter 11. The Essence of Resilience against Disaster: Requirements for Geographic Education -- Chapter 12. Common Features of Business Resilience in Japanese Companies -- Chapter 13. Resilience of Earth System -- Chapter 14. Concluding chapter: What is (3z(BResilience(3y(B?.s
Keywords: Regional economics; Spatial economics; Social policy; Corporate governance; Industrial management$1 (BEnvironmental aspects.s; Business ethics; Risk management; Regional/Spatial Science; Social Policy; Corporate Governance; Sustainability Management; Business Ethics; Risk Management